PROGRAM MA’HAD AL-JAMI’AH IAIN CURUP: SOLUSI MENGATASI RENDAHNYA KEMAMPUAN MAHASISWA MEMBACA AL-QUR’AN - Rapia Arcanita (Badan Litbang dan Diklat Kementerian Agama RI, 2021)
AbstractIAIN Curup, as an Islamic higher education institution, demands the students to master al-Qur'an. One of the steps towards the mastery of the Qur’an is through the activities of tahsin (reciting) al-Qur'an implemented by Ma'had al-Jamiah (college dormitory) of IAIN Curup. Therefore, this study aimed to see the role of Ma'had al-Jamiah of IAIN Curup in overcoming the students' low mastery of al-Qur'an, by paying attention to the results of Ma'had al-Jamiah programs consisting of the practicum of tahsin al-Qur'an and students’ worship practicum. These activities already ran for three semesters. However, it was still found the students who could not read al-Qur'an well and could not perform the prayers properly. This study employed a qualitative approach. The data were obtained from interviews, observations, and documentation, which were then analyzed by using a qualitative approach. Thus, the following conclusion was drawn: First, the Ma'had Al-Jami'ah programs were quite representative in improving students’ mastery of al-Qur’an; Second, ma'had activities applied a semi-Islamic boarding school education model in a classical form; Third, Ma'had al-Jamiah’s policies concerning the subjects of Tahsin Al-Qur’an, Worship Practicum I, and Worship Practicum II as the requirements to take part in KPM (Community Service Program), PPL (pre-service teaching program), Internship, comprehensive exams, and Munaqasyah (thesis exams) really stimulated students to master reciting al-Qur'an.AbstrakIAIN Curup sebagai lembaga pendidikan tinggi Islam, dituntut agar mahasiswanya mengusai al- Qur’an. Salah satu langkah menuju kemampuan penguasaaan al-Qur’an tersebut adalah melalui kegiatan tahsin al-Qur’an sebagai mana yang di laksanakan oleh Ma’had al-Jamiah IAIN Curup. Oleh karena itu penelitian ini berusaha melihat peran ma’had al-Jamiah IAIN Curup dalam mengatasi rendahnya penguasaan al-Qur’an mahasiswa IAIN Curup, dengan memperhatikan hasil kegiatan Ma’had yang mencakup praktikum tahsin al-Qur’an dan praktikum ibadah kemahasiswaan. Kegiatan tersebut sudah berjalan selama tiga semester. Namun masih ditemukan mahasiswa belum bisa membaca al-Qur’an dengan baik dan belum bisa melaksanakan ibadah shalat dengan baik. Penelitian ini menggukanakan pendekatan kualitatif. Data diperoleh dari hari hasil wawancara, pengamatan dan dokumentasi, selanjutnya dianalisis dengan pendekatan kualitatif sehingga diperoleh simpulan: Pertama Program Ma’had Al-Jami’ah cukup representatif dalam meningkatkan kompetensi mahasiswa di bidang al-Qur’an; Kedua kegiatan ma’had menawarkan menerapkan model pendidikan semi pondok pesantren dalam bentuk klasikal; Ketiga Ma’had al- Jamiah IAIN Curup menjadikan ketiga materi (Tahsin al-Qur’an, Praktek Ibadah I dan II sebagai syarat untuk bisa mengikuti KPM, PPL, Magang, Komprehensif dan sidang Munaqasyah) sangat memacu mahasiswa dalam penguasaan bacaan al-Qur’an.